The influences of rugby spin pass technique on movement time, ball velocity and passing accuracy - Worsfold, P. R.; Page, M. (International Journal of Performance Analysis in Sport, 2014)
The success of a rugby spin pass is determined by the speed of the passing movement and the resultant velocity, distance and accuracy of the ball flight. the present study investigated 900 dominant and 900 non-dominant hand spin passes at three randomised target distances (4, 8 and 12 m), whilst players ran between 60 and 80% of their maximum speed. two distinct types of spin pass technique were compared. one involved the player lowering their body height ('body drop') then raising it again prior to ball release, and the other, players maintained a more upright body position and incorporated greater arm movement. the current study assessed performance measures (velocity, spin, timing, accuracy) of the two previously identified passing techniques made from the players' dominant and non-dominant hands. the percentage of passes which included a 'body drop' phase rose linearly with pass distance. the 'body drop' technique resulted in higher ball velocities and improved accuracy from both the dominant and non-dominant passing hands. in comparison, the more upright passing technique resulted in a faster passing movement, but was compromised by lower ball velocity and accuracy. the findings provide an understanding of how different spin pass techniques affect the mechanics of ball flight and performance.